The undoing-hypothesis in athletes - three pilot studies testing the effect of positive emotions on athletes' psychophysiological recovery. (May 2023) - Lautenbach, Franziska; Zajonz, Pia
Abstract: Three pilot studies were performed to investigate the undoing-hypothesis (i.e., fast psychophysiological recovery due to positive emotions after stressor) in an athletic sample – after 1) a psychosocial stressor (study 1, N  = 19), 2) a physiological stressor (study 2, N  = 14), and 3) a simulated competition (study 3, N  = 13). Therefore, the effect of positive emotion interventions on cardiovascular (heart rate, blood pressure, heart rate variability) and psychological (perceived positive and negative emotions, arousal, valence) recovery was tested in comparison to neutral interventions. Additionally, study 3 examined the impact on performance after the intervention. Results only confirmed the undoing-hypothesis after a psychosocial stressor (study 1), showing greater increases in perceived positive emotions and a long-lasting decline in diastolic blood pressure after the positive emotion induction compared to the neutral condition. No effects on performance were found. Despite missing significance, descriptive analyzes indicated that our results are in line with the undoing-hypothesis, calling for further research in a greater sample to explore its full potential for athletes. Especially its impact on performance should be examined in future studies. Highlights: Testing the potential of the undoing-hypothesis for athletes. Significant support for the undoing-hypothesis was found after a psychosocial stressor. An effect of positive emotions on the emotional state and on diastolic blood pressure after psychosocial stress was found. In a simulated competition descriptive results indicate a decline in arousal due to the positive emotion intervention. The study gives recommendations for future research to examine the potential of the undoing-hypothesis for athletes.